Towards a more sustainable financing of small farmers and fisherfolk's agricultural production - Connie Bayudan-Dacuycuy; Marife Magno-Ballesteros; Lora Kryz C. Baje; Jenica A. Ancheta (Philippine Institute for Development Studies (PIDS), 2020)
Cognizant of the value and contribution, as well as of the challenges in the agricultural finance, the government has intensified its lending programs designed to help the agricultural sector, specifically, the smallholders. Thus, affordable and easy access retail lending has intensified in recent years. Despite these efforts, significant problems remain. These include the lack of markets and low prices, which have significant implications on the overall repayment capacity and credit rating of the small farmer and fisherfolk (SFF). Indeed, these lending programs are unlikely to become successful if financing and production are not viewed in the bigger context of a value chain financing. Thus, this paper looks into the SFF's financing ecosystem and provides recommendations on how the existing value chain financing can become more inclusive and sustainable.
Keywords: 330; Agricultural value chain financing; small farmer and fisherfolk; Philippines